Eutectic ionic liquid mixtures and their effect on CO2 solubility and conductivity1. Issue 63 (10th July 2015) - Ivanova, Anna S.; Brinzer, Thomas; Roth, Elliot A.; Kusuma, Victor A.; Watkins, John D.; Zhou, Xu; Luebke, David; Hopkinson, David; Washburn, Newell R.; Garrett-Roe, Sean; Nulwala, Hunaid B.
<x xml:space="preserve">Abstract</x> A simple binary system of compounds resembling short-chain versions of popular ionic liquids has been shown to have alloying properties.